Association of High Birth Weight With Incident Heart Failure in the ARIC Study. Issue 9 (7th May 2019) - Rashid, Abdirahim; Agarwala, Anandita; Novak, Eric; Brown, David L.
Abstract : Background: Traditional risk factors for heart failure––coronary heart disease, hypertension, diabetes mellitus, obesity, and smoking––only account for about 50% of cases. Thus, the identification of novel risk factors is of significant public health importance. As high birth weight infants are at increased risk for obesity and diabetes mellitus later in life, which are both risk factors for the development of heart failure, we sought to assess the association of high birth weight with incident heart failure in the ARIC (Atherosclerosis Risk in Communities) study. Methods and Results: The ARIC study is a biracial prospective community‐based investigation of 15 792 individuals aged 45 to 64 years at baseline. Study participants who were born premature or born a twin were excluded from this analysis, resulting in 9820 participants who provided either their birth weight category (low, medium, high) or exact birth weight. After adjusting for differences in demographics, risk factors, and comorbidities, compared with medium birth weight, those with high birth weight had a significantly increased risk of incident heart failure (hazard ratio, 1.27; 95% CI, 1.05–1.54 [ P =0.014]). The hazard for all‐cause mortality for high birth weight compared with medium birth weight was 1.16 (95% CI, 0.99–1.34; P =0.06). There was no association of high birth weight with myocardial infarction (hazard ratio, 1.06; 95% CI, 0.84–1.34 [ P =0.6]). Conclusions: High birth weight was associated with a significantly increased hazard of incident heart failure independent of traditional risk factors and a trend toward an increased hazard of death. A history of high birth weight should be ascertained in young adults for primordial prevention of heart failure and in older adults for primary prevention.